«Noi li chiamiamo ragazzi»: le violente ingenuità discorsive del babytalk. Spunti per un’analisi dei processi comunicativi nei servizi per disabili intellettivi - Pistone, Francesca (AM. Rivista della Società Italiana di Antropologia Medica, 2020)
"We call them kids”: The Naive Violence of Babytalk. Ideas for an Analysis of Communication Processes in Services for the Intellectually Disabled In the daily life of rehabilitation practices, designations often reveal an implicit classificatory thought: we speak of disabled people as if they were entities independent of the networks of historical and epistemological relationships in which they are inserted together with their caregivers. In this paper we aim at tracing these cultural entanglement through a case-study analysis of discursive and performative infrastructures within an Adult Dis-abled Service in Rome, especially focusing on baby-talk practices in the relational exchanges between users and operators. Through a constant analysis of his underlying communicative and ethnopragmatic status, the researcher-operator takes himself part of this linguistic game, getting bound to an implacable ethnographic reflexivity. Nevertheless, we argue that the political and procedural role of these gestures in the construction of institutional linguistic walls cannot be fully understood without taking into account the power of public health as a privileged place in the production of meanings and change. "Noi li chiamiamo ragazzi”: le violente ingenuità discorsive del babytalk. Spunti per un’analisi dei processi comunicativi nei servizi per disabili intellettivi Nella quotidianità delle pratiche riabilitative le designazioni rivelano spesso un pensiero classificatorio implicito: si parla di disabili come fossero entità indipendenti dalle reti di relazioni storico-epistemologiche nelle quali sono inseriti insieme ai loro caregiver. L’intervento si propone di ripercorrere tali azioni culturali in un Servizio Disabili Adulti di una Asl di Roma. Infrastruttura discorsiva e performativa, il babytalk praticato negli scambi relazionali tra utenti e operatori, diventa un gioco linguistico al quale anche il ricercatore-operatore prende parte, vincolandolo a una implacabile riflessività etnografica, attraverso un’analisi costante dello statuto comunicativo ed etnopragmatico sotteso. La valenza politica e processuale di questi gesti, nella costruzione di muri linguistici istituzionali, tiene tuttavia conto del potere della sanità pubblica come luogo privilegiato nella produzione di significati e cambiamento.